Tantangan Pendidikan di Era Postmodernisme - Rahman, Fathur (Al-Riwayah : Jurnal Kependidikan, 2017)
This paper discusses three major issues, namely how the image of the objective conditions of Islamic education, age and postmodernism as an intellectual thought movement that could be a challenge as well as how the strategic steps that should be taken to realize the civil society Muslims in Indonesia. Factually, renewal of Islamic education becomes an absolute necessity is manifested as a significant prerequisite in creating Muslim intelligent, energetic resources, committed against Islam and good manner. The other hand, it has become anticipation and protection against any negative thoughts brought postmodernism in various variants, for example: humanism, liberalism, asceticism (spirituality) and so on. The other side becomes a tool device as a prerequisite to realize an order of civil society in this millennium era. It shall be the duty and responsibility of moral, social, intellectual and great historical that should be fulfilled by the Muslims in general and for the upper middle class in particular.